Modeling and analysis of a single-phase core-type transformer under inrush current and nonlinear load conditions - Altun, Huseyin; Sunter, Sedat; Aydogmus, Omur (Springer, 2021)
In this paper, a transformer model based on the equivalent electrical circuit considering the nonlinearity of the iron core has been developed. The nonlinear behavior of the iron core was taken into account by using the inverted Jiles-Atherton hysteresis model. The single-phase core-type transformer was analyzed under different energization, remnant flux for inrush current and nonlinear load conditions. Illustrative and remarkable simulation and experimental results related to inrush current along with the primary and secondary currents under nonlinear load conditions were demonstrated. In addition, magnetic flux in the iron core and the hysteresis curve as a consequence of the relation of the magnetic flux and magnetizing inrush current were demonstrated. Operation of the transformer under various nonlinear load conditions have been demonstrated with simulation and experimental results. Variation of peak value of the inrush current for different levels of remnant flux in the iron core and different switching-on angles of the voltage applied to the primary was further indicated.
Keywords: Inrush current; Jiles– Atherton hysteresis model; Transformer modeling